Políticas de género en El beso de mujer araña de Manuel Puig - Soboniak, Katarzyna (Romanica Silesiana)
Gender politics in The Kiss of the Spider Woman by Manuel Puig The objective of the present work is to study the constructions of sexual identities that are found in The Kiss of the Spider Woman by Manuel Puig. In order to clarify this concept, it is important to contextualize the book in its period, its area of political conflicts that were present in Argentina in the 70s, as well as in the significantly phallic-centered society. Subsequently, through the use of dichotomies, the text will analyze the problem of the rigidity of the binary logic and, at the same time, will present new forms of gender-sexual constructions. Finally, this article will investigate the notion of homosexuality as a transgressive practice that questions the hegemonic discourse of heterosexuality seen and understood as the only legitimate orientation. Key words: Manuel Puig, gender, sexuality, heterosexual hegemony, politics.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />